Identity Assertion by the Bodos of North East India: Exploring the Role of the Educated Middle Class (Global Journal of Human-Social Science, 2014)
The paper examines the different phases of identity assertion by the Bodos the largest plains tribe of Assam a state situated in Northeast India Available evidence indicates that the emerging educated middle class has been playing a catalytic role in articulation of Bodo identity in various phases It observes that the Assam movement against foreign nationals failed to accommodate the aspirations of smaller nationalities like Bodos and argues that as the Bodo middle class has been apprehensive of Assamese middle class hegemony it sought to carve out its own political space by transforming and consolidating Bodo ethnic and regional identity into a distinct national identity and by raising the demand for a separate homeland for protection of its class interests The paper proposes to examine the dynamics of this phenomenon